Determinan Keputusan Membayar Zakat pada BAZNAS dan LAZ: Studi Bibliometric VOSviewer dan Literature Review - Faruq, Muhammad Al; Putra, Yuniarti Hidayah Suyoso (Jurnal Samudra Ekonomi dan Bisnis, 2024)
The research aims to map and analyze the determinants of the decision to pay zakat to BAZNAS and LAZ over a period of 10 years starting from 2013 to 2022. This research uses a mix-method approach, namely a quantitative method with a study of bibliometric VOSviewer and a qualitative method with a study of literature review. Secondary data was collected from the Google Scholar site, and analyzed using the Microsoft Excel, VOSviewer, Mendeley Desktop and Publish or Perish 8 programs. The results showed that there were 60 SINTA indexed published journal articles from 2013 to 2022, the mapping from the VOSviewer study of bibliometrics were divided into 10 clusters and 66 topics, and the mapping from the study of literature review show 30 variable topics.